The Tabot Festival in Bengkulu Indonesia : Synergy between Culture, Religion and Socioeconomic Empowerment - Ulfa, Fadillah; Jalili, Ismail (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
This study investigates the Tabot Festival in Bengkulu Indonesia focusing on its cultural, religious and sosioeconomic impacts, with the aim of demonstrating how local traditions can both preserve cultural heritage and empower the community economically. The study involves examining the festival's transition from a Shiite religious ceremony commemorating Imam Husein bin Ali’s martyrdom, to a broader cultural celebration that attracts significant tourism. Employing a qualitative ethnographic method, data were analyzed through extensive literature reviews. The findings reveal that the festival retains its deep cultural and religious roots, reflecting humanitarian and Islamic values such as courage, sacrifice and justice through its rituals and processions. Despite its evolution into a lively cultural event, the festival continues to uphold significant Islamic traditions and symbols. Economically, the Tabot Festival provides substantial benefits to the local economy, boosting sectors such as hospitality, restaurants and transportation. It also creates a multiplier effect by stimulating the creative economy and generating temporary employment opportunities for vendors, artisans and service providers. The local community's active participation further strengthens social cohesion and economic welfare.